PENERAPAN AGILE DEVELOPMENT METHODOLOGY PADA SISTEM INFORMASI PENJUALAN ECER DAN GROSIR TOKO KINANTI MARTAPURA - Wisnumurti, Wisnumurti; Trimarsiah, Yunita; Faulina, Sri Tita (JUTIM (Jurnal Teknik Informatika Musirawas), 2022)
With current tehnological developments, the application of the agile development methodology is an interesting field of sales information systems in the business world to study in the digital world. The development of this method is a development that is more efficient to apply and one of the topics that has been studied quite a lot by researchers researchers in the field of computer science. The Kinanti Sembako Store has a problem, namely in the transaction and stock recording section, where in that section they still carry out manual calculations using a book as inventory, in every activity such as recording transactions, stock, data search and reporting is not effective and efficient. The method used in the development of a sales information system is the Agile Development methodology which is a system development method that is focused on the user, the stages of the Agile Development methodology are system analysis, design, application development, testing, application deployment, revision and evaluation. , as well as system maintenance. In addition to the application development method, there is also an application testing method, namely using black box testing as a test of application functionality. The purpose of doing research is to make it easier to process data and present information in the form of inputting, managing, and making reports on goods data, customer data, purchase transaction data, sales transaction data, and profit and loss, so that with this information system it is hoped that the problems that occur in the company can be overcome .. Keywords : black box, Inventory, efficient information system,